Memulihkan Hukum Adat Sebagai Sumber Hukum Dalam Pembangunan Sistem Hukum Indonesia - Zuhdi Arman; Daria Daria (P3M dan Jurusan Syariah dan Ekonomi Bisnis Islam STAIN Sultan Abdurrahman Kepulauan Riau, 2022)
The ideas contained in living legal theory include the statement that in the process of determining laws and regulations it is necessary to pay attention to the values and norms of law that live and are applied in society. If the application of laws that are contrary to values and norms or laws that depend and apply in society, then of course it will be handled appropriately. In the Indonesian context, the right to life of indonesian people is customary law. The position of Indigenous law is the right to live among indigenous peoples in Indonesia.The method used is a type of qualitative descriptive analysis. From the results of this analysis is the national development policy against customary law has now been officially recognized by the State of its existence, but its use is limited. The exercise of Ulayat's rights and similar rights of indigenous peoples, while still in fact having to be carried out in such a way that it is in accordance with national and public interests, which is based on the unity of the nation and will not conflict with other supreme laws and regulations in accordance with the urgency of restoring Indigenous law as the basis for national development policy. It is expected to the government and also indigenous peoples, in order to still make customary law as a source in the life of the state, therefore customary law remains maintained and sustainable throughout the time.